Corticospinal adaptations to strength training and its associations to rate of force development - Enroth, Miro (2022)
Introduction. Neuromuscular determinants underlying rate of force development during rapid muscle contractions may be more relevant compared to maximal strength in many athletic events characterized by power and speed, as well as in clinical relations with older adult and patient populations. Earlier studies have described various neuromuscular determinants associated with rapid muscle contractions, and while rate of force development is affected by both intrinsic neural and contractile properties the neural determinants seem to be particularly important at the onset and up to 75 milliseconds into rapid contractions. Variety of strength training modalities have been demonstrated to improve both the neural properties and rate of force development, and many associations between the two are evident. However, majority of strength training studies have addressed the associations considering the whole corticospinal tract but not in smaller segments. Therefore, the objective of this study was to investigate potential differences separately at cortical and spinal level.